Corporate Social Responsibility and Societal Governance: Lessons from Transparency in the Oil and Gas Sector - Frynas, Jędrzej George (Journal of business ethics, 2010)
This article evaluates the potential of the current Corporate Social Responsibility (CSR) agenda for addressing issues related to societal governance. The investigation focuses on the experience of the oil and gas sector, which has been among the leading industry sectors in championing CSR. In particular, the article analyses the issue of revenue transparency, which has been the principal governance challenge addressed by multinational oil and gas companies. The article suggests that (1) tackling governance challenges is crucial to addressing the impact of corporate activities; (2) current CSR and policy initiatives are entirely insufficient in addressing governance challenges and (3) corporate activities may be contributing to governance failures.